Homeland Fascism Corporatist Government in the New American Century - Schwendinger, Julia (punctum books, 2016)
"It can't happen here." This has been the prevailing sentiment about the possible emergence of fascism in the United States since the rise of international fascism in the 1930s. Yet there are signs that it may already be happening, and at the highest levels of government... In their copiously researched and documented work the Schwendingers outline the structural transformations, policies, and practices that raise the prospect of fascist governance in the 21st Century US. They show that a homeland fascism has significant supports within the framework of American liberal democracy. This is an important analysis in a context in which concerns about fascist demagoguery and far right mobilization appear to be growing in the US and beyond.